Peluang Implementasi Teknologi Big Data Dan Block Chain Untuk Peningkatan Kinerja Perdagangan Pada Sektor UMKM di Indonesia Pada Era Industri 4.0 - M Zaky Hadi (Cendekia Niaga, 2019)
Industry 4.0 is the main challenge in business environment resulted from disruption technology. It has been affected many sectors in development country including SME in Indonesia. This paper provides a literature review on big data and block chain implementation opportunity to increase trading performance for indonesian SME sector in industry 4.0 era. A systematic literature review (SLR) was implemented to review the literature analysis, provide gap and recommendation to future research and managerial implementation on Indonesian SME. We found a system development on Big Data and how Indonesian government implements the system is the main challenge in this research area.